Elevated expression of microRNA-155, microRNA-383, and microRNA-9 in Iranian patients with polycystic ovary syndrome - Maryam Faraji; Kambiz Roshanaei; Hamed Afkhami; Nasrin Heidarieh (Biochemistry and Biophysics Reports)
Background and objective: Polycystic ovary syndrome (PCOS) is a complex endocrine disorder with both genetic and environmental components. Recent studies have highlighted the potential role of microRNAs (miRNAs) and single nucleotide polymorphisms (SNPs) in its pathogenesis. This study aimed to investigate the association of three SNPs (rs2252673, rs2272046, and rs1894116) in the INSR, HMGA2, and YAP1 genes, respectively, with PCOS, as well as the expression levels of miR-155, miR-383, and miR-9 in Iranian patients. Methods: We included 100 PCOS patients and 100 healthy controls. DNA and RNA were extracted from blood samples. SNP genotyping was performed using tetra-primer ARMS-PCR, while miRNA expression levels were quantified using quantitative reverse transcription PCR (qRT-PCR). Logistic regression and ANOVA tests were used for statistical analysis, and Pearson's correlation test (PcT) was applied to assess relationships between miRNA expression profiles. Results: No significant associations were observed between the investigated SNPs (rs2252673, rs2272046, and rs1894116) and PCOS risk. However, logistic regression analysis revealed a significant difference for rs1894116 under dominant (P = 0.045) and recessive (P = 0.001) models. Notably, the expression levels of miR-155, miR-383, and miR-9 were significantly upregulated in PCOS patients compared to controls, with fold changes of 13.5, 4.13, and 10.7, respectively (P < 0.05). Limitations: This study has several limitations, including the relatively small sample size (n = 100 per group) and the ethnic-specific nature of the population studied, which may limit generalizability to other populations. Conclusion: Our findings suggest that miR-155, miR-383, and miR-9 are significantly upregulated in Iranian PCOS patients, highlighting their potential as biomarkers or therapeutic targets. However, no significant associations were found between the investigated SNPs and PCOS risk. Future studies with larger, multi-ethnic cohorts are warranted to validate these findings and explore the molecular mechanisms underlying the roles of these miRNAs in PCOS pathophysiology.